The Three Pillars Paradigm: Islamic Education Management between Kiai, Curriculum, and Community - Lukman Hakim Lukman (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2025)
This study aims to explore the three-pillar paradigm in Islamic education management, encompassing the strategic role of the kiai (Islamic scholar-leader), curriculum alignment, and active community involvement. These three components constitute fundamental pillars in the governance of Islamic educational institutions, particularly in pesantren and community-based madrasahs. The research employs a descriptive qualitative approach, utilizing data collection methods including field observation, in-depth interviews, and document analysis. The findings reveal that the kiai functions not only as a spiritual leader but also as a managerial and visionary figure who determines institutional direction, policies, and foundational educational values. The curriculum is designed to be contextual and flexible, adapting to contemporary developments while maintaining its rootedness in Islamic scholarly traditions. Meanwhile, the community plays a significant supporting role, contributing to moral, social, and material aspects. These three actors engage in synergistic interactions that reinforce the sustainability and relevance of the Islamic education management system. The study concludes that collaboration among these key actors is a fundamental prerequisite for developing a participatory, value-based, and contextually grounded model of educational management.